What happened with the application of time and motion study in the last two decades?: review of the literature - Ovalle-Castiblanco, Alex Mauricio; Cárdenas-Aguirre, Diana María (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2016)
The time and motion study is an industrial engineering technique that seeks to increase the productivity of organizations, systematically eliminating operations that do not add value to the process and constitutes the basis for the standardization of operating times. This paper aims to identify the application that the time and motion study has had over the past two decades, as well as techniques and tools most used and the sectors to which has been applied. For which they were consulted databases and direct science web of science and technology network analysis tool called citation tree of science, developed at the National University of Colombia in Manizales was used. From the analysis it was determined that the time study with stopwatch, applied in its traditional form, is most often used for measuring tasks technique, additionally a marked tendency to conducting presents research in the health sector.